Feasibility of Free-breathing CCTA using 256-MDCT. Issue 27 (July 2016) - Liu, Zhuo; Sun, Ye; Zhang, Zhuolu; Chen, Lei; Hong, Nan
Abstract : Abstract: Usually, coronary computed tomography angiography (CCTA) is performed during breath-holding to reduce artifact caused by respiration. The objective of this study was to evaluate the feasibility of free-breathing CCTA compared to breath-holding using CT scanner with wide detector. To evaluate the feasibility of CCTA during free-breathing using a 256-MDCT. In 80 patients who underwent CCTA, 40 were performed during breath-holding (group A), and the remaining 40 during free-breathing (group B). The quality scores for coronary arteries were analyzed and defined as: 3 (excellent), 2 (good), and 1 (poor). The image noise, signal-to-noise ratio and effective radiation dose as well as the heart rate variation were compared. The noise, signal-to-noise ratio, and effective radiation dose were not significantly different between the 2 groups. The mean heart rate variation between planning and scanning for group A was 7 ± 7.6 bpm, and larger than 3 ± 2.6 bpm for group B ( P = 0.012). Quality scores of the free-breathing group were better than those of the breath-holding group (group A: 2.55 ± 0.64, group B: 2.85 ± 0.36, P = 0.018). Free-breathing CCTA is feasible on wide detector CT scanner to provide acceptable image quality with reduced heart rate variation and better images for certain patients.